2021
DOI: 10.1038/s41467-021-25231-0
|View full text |Cite
|
Sign up to set email alerts
|

On the molecular origins of the ferroelectric splay nematic phase

Abstract: Nematic liquid crystals have been known for more than a century, but it was not until the 60s–70s that, with the development of room temperature nematics, they became widely used in applications. Polar nematic phases have been long-time predicted, but have only been experimentally realized recently. Synthesis of materials with nematic polar ordering at room temperature is certainly challenging and requires a deep understanding of its formation mechanisms, presently lacking. Here, we compare two materials of si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 63 publications
4
72
2
Order By: Relevance
“…MD simulations showed that in the absence of the field the polarization is parallel to the average orientation of the molecules. 20 However, the polar order of molecular axis measured by = 〈 ( )〉 where is the angle between the director and the molecular axis is larger than the polar order calculated for the direction of the dipoles. That the two order parameters are different is expected because the molecular long axis and the dipole are not parallel (Fig.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…MD simulations showed that in the absence of the field the polarization is parallel to the average orientation of the molecules. 20 However, the polar order of molecular axis measured by = 〈 ( )〉 where is the angle between the director and the molecular axis is larger than the polar order calculated for the direction of the dipoles. That the two order parameters are different is expected because the molecular long axis and the dipole are not parallel (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…. RM734 has a very large dipole moment (11.4 D) as calculated at the M06HF-D3/aug-cc-pVTZ level of DFT, at an angle of 18.3° with respect to the molecular axis and is therefore mainly longitudinal 20. Fig.1.b…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…In 2017 two materials were reported -RM734 5 and DIO 6 -that are now understood to have polar nematic order and are ferroelectric, over a century after Born's conjecture. [7][8][9] This so-called ferroelectric nematic (NF) phase displays a slew of unique properties: ferroelectric properties with huge spontaneous polarisation, 8,10 giant dielectric anisotropy, polar domains, 10 strong non-linear optical response, 11 unique electrooptic responses, 12 and thermal gradient-induced circular motion of particles, 13 to name a few. The remarkable properties of the NF phase, coupled with fluidity and relative ease of alignment 14 , will ensure this field flourishes in the decades to come.…”
Section: Introductionmentioning
confidence: 99%
“…The type and place of lateral substitution in molecular core play a crucial role [59][60] as the -electron density of substituted aromatic rings, which is strongly influenced by the character of atom used for substitution, affects the intermolecular interactions (packing) in smectic layers of ferroelectric SmC* phase due to donor-acceptor coupling. However, in the cases, when the lateral substitution is placed far from a chiral centre, the direct influence upon the chiral centre is not expected.…”
Section: Introductionmentioning
confidence: 99%